The power and the misuse of power by China's local procuratorates in anticorruption. (June 2016) - Li, Fenfei; Deng, Jinting
Abstract: Previous literature mainly blames the party commission's leadership and the CDI's leading role in anticorruption for China's procuratorate's ineffective anticorruption work, which only reflects part of the picture. This article has analyzed the interactions between local procuratorates and other entities in anticorruption based upon findings from interviewing prosecutors, CDI officers, and suspects, and conducting content analysis of internal records and files, procedural and substantive rules regarding anticorruption and the work of the procuratorate. It argues that there exist balances between local procuratorates and other entities; and local procuratorates have strong institutional motives from the evaluation system, fundraising needs and legal loopholes to manipulate and transact the power in investigating and prosecuting corruption cases with little supervision, which contributes to the selective prosecution and light sentence in corruption.